Determinan Pengangguran Lulusan SMK di Indonesia Tahun 2020 - Miko Oktavio Wijaya; Efri Diah Utami (Seminar Nasional Official Statistics, 2021)
Indonesia is facing a demographic bonus phenomenon, but the Open Unemployment Rate (TPT) in Indonesia is still high. Vocational High School (SMK) graduates have become the biggest contributors to TPT in Indonesia in the last 5 years. This condition isn’t accordance with PP No. 17 of 2010 which states that vocational education aims to create graduates who are ready to work. This study aims to find the general description of unemployment for SMK graduates, identify the variables that cause SMK graduates become unemployment and determine the tendency of the variables used. The data used is Sakernas February 2020. The analytical method used consists of descriptive analysis and inferential analysis using binary logistic regression. The results showed that the variables of gender, disability disorder, field of expertise, year of graduation, and participation in training had a significant effect on the unemployed status of SMK graduates. The tendency for SMK graduates to experience unemployment is higher for male graduates, do not have disabilities, come from other fields of expertise, graduated within a year, and have never attended training.